(untitled) - Moore, David S. (New York, NY, 2007)
This book offers a number of innovations, including briefer chapters, a new problem-solving process, a wealth of new exercises, and new all-in-one place StatsPortal, with all the electronic tools instructors and students need
Keywords: Statistics,Thống kê